Improved ethanol tolerance and production of Saccharomyces cerevisiae by global transcription machinery engineering via directed evolution of the SPT8 gene. Issue 2 (3rd April 2019) - Xue, Ting; Chen, Duo; Su, Qiuqiong; Yuan, Xue; Liu, Kui; Huang, Luqiang; Fang, Jingping; Chen, Jiebo; He, Wenjin; Chen, Youqiang
ABSTRACT: Ethanol tolerance involves complex interactions of several genes in the Saccharomyces cerevisiae genome that encodes proteins that are the subunits of the SAGA (Spt-Ada-Gcn5-acetyltransferase) complex, particularly those that interact with the TATA-binding protein. Global transcription machinery engineering has been used to reprogram the transcription levels of multiple genes to change cellular phenotypes important for technological applications by altering key proteins by error-prone polymerase chain reaction (epPCR) mutations. In this study, we produced S. cerevisiae mutants from the wild-type wine yeast Y01 strain by directed evolution of the SPT8 (suppressor of ty insertions 8) gene using epPCR combined with construction and overexpression of the constructed pUPST mutant library for improved ethanol tolerance and production. We found that the mutant strains gave 8.9% higher ethanol tolerance and 10.8% higher ethanol production than the wild-type. The desired phenotype resulted from the combined effect of two separate mutations in SPT8, which caused serine to replace phenylalanine (Asn 156 His) and glycine to replace serine (Gly 585 Ser) in the encoded SPT8 protein.